2012
DOI: 10.3402/gha.v5i0.19099
|View full text |Cite
|
Sign up to set email alerts
|

The effect of distance to formal health facility on childhood mortality in rural Tanzania, 2005–2007

Abstract: BackgroundMajor improvements are required in the coverage and quality of essential childhood interventions to achieve Millennium Development Goal Four (MDG 4). Long distance to health facilities is one of the known barriers to access. We investigated the effect of networked and Euclidean distances from home to formal health facilities on childhood mortality in rural Tanzania between 2005 and 2007.MethodsA secondary analysis of data from a cohort of 28,823 children younger than age 5 between 2005 and 2007 from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
79
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 24 publications
10
79
1
3
Order By: Relevance
“…A study of Demographic Health Survey (DHS) data from the DRC in 2007 found unexpected geographic patterns in under-5 mortality, and highlights subnational areas where a potential confluence of individual, household and environmental elements affecting child mortality may be spatially clustered [42]. Studies in rural Tanzania and Burkina Faso found that physical access to health facilities was associated with child mortality [43,44]. A study of the spatial distribution of under-5 mortality across and within 20 African countries using data from the late 1970s to the early 1990s ascribed geographic patterns to similar disease environments in eastern Africa and to economic development along the coast of western Africa [12].…”
Section: Introductionmentioning
confidence: 99%
“…A study of Demographic Health Survey (DHS) data from the DRC in 2007 found unexpected geographic patterns in under-5 mortality, and highlights subnational areas where a potential confluence of individual, household and environmental elements affecting child mortality may be spatially clustered [42]. Studies in rural Tanzania and Burkina Faso found that physical access to health facilities was associated with child mortality [43,44]. A study of the spatial distribution of under-5 mortality across and within 20 African countries using data from the late 1970s to the early 1990s ascribed geographic patterns to similar disease environments in eastern Africa and to economic development along the coast of western Africa [12].…”
Section: Introductionmentioning
confidence: 99%
“…5,6 These barriers are thought to contribute to increased child mortality, for instance long distance from a health facility increased mortality risk by 17% in Tanzania. 7 Malnutrition, previous hospitalizations and HIV are often identified as key risk factors for post-discharge mortality. 4 While these risk factors may assist clinicians in the identification of vulnerable children, many other contextual and social factors may contribute to post-discharge mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Para los estudios de mortalidad infantil se consideran, como variables para el control de confusión, principalmente condiciones de antecedentes perinatales tipo multiparidad, periodo intergenésico y número de partos previos y, en menor medida, condiciones sociales tipo etnia, ausencia de la madre y su nivel educativo. Por último, en relación con la mortalidad en la niñez se identificó asociación significativa en ocho estudios, con un riesgo entre quienes habitan a mayor distancia que podría ser tan bajo como 1,02 veces el riesgo de quienes habitan a menos de 2 horas de camino en Tanzania [45], y no mayor a 4,43 veces el riesgo de quienes habitan a menos de 5 km en Gambia [15]. Si bien este es el grupo de edad con mayor cantidad de estudios realizados, es también el que muestra resultados más heterogéneos.…”
Section: Revisión Sistemáticaunclassified
“…De forma contraria, las publicaciones basadas en diseños de cohorte o longitudinal, a partir de las cuales se obtuvo una estimación de 1,32 (IC95% 1,04-1,67), presentaron varianza significativa (valor p < 0,01) y de alto impacto en la interpretabilidad de la medida resumen (I 2 = 86%). La heterogeneidad observada entre estos últimos artículos también está relacionada con la diferencia particular en el resultado del trabajo de Zaman [15], la cual es más del doble de las estimaciones de Schoeps [51] y Kadobera [45].…”
Section: Análisis De Sensibilidadunclassified